Mycobacterium avium subsp. paratuberculosis and Hashimoto’s thyroiditis: Is MAP the trigger? - Moghadam, Maedeh; Ghaemi, Ezzat Allah; Akbari, Hamideh; Razavi Nikoo, Hadi; Zamani, Samin (Frontiers in Cellular and Infection Microbiology, 2022)
Hashimoto's thyroiditis (HT) is an autoimmune disorder of the thyroid gland that can cause hypothyroidism. As HT is a multifactorial disorder, activation of immune responses in genetically predisposed individuals exposed to some environmental factors can contribute to it. Microorganisms, as environmental factors, include Mycobacterium avium ssp. paratuberculosis (MAP) by molecular mimicry can be important in this autoimmune disorder. This study aimed to investigate the association between MAP and HT. This case-control study included 110 participants consisting of 60 HT patients and 50 Healthy Controls (HCs). Blood samples were collected. Nested-PCR of the IS900 gene determined the presence of MAP DNA. Enzyme-linked Immunosorbent Assay (ELISA) was designed to identify antibodies (Abs) against the MAP3865c epitope, which has a homologous sequence with ZnT8 in the sera. Demographic information of all participants was recorded. Anti-TG, Anti-TPO, TSH, anemia, and ruminant exposure were higher in HT patients than in the HCs (p <0.05). MAP IS900 was detected significantly more in the patients (46.6% consisting of 30%, 8.3%, and 8.3% in clinical, subclinical, and unknown) than in the HCs (14%). Sera showed a remarkable frequency of reactivity against MAP3865c in the patients (38.3%) in comparison to the HCs (10%) (p=0.0001). Furthermore, a significantly higher rate of livestock contact and traditional dairy consumption was found in individuals with MAP or anti- MAP3865c Abs positive result (p <0.05). This study suggests a possible link between MAP and HT. These findings indicated that MAP frequency was not statistically different in the severity of HT and its shift into clinical and subclinical forms; therefore, it could be assumed that MAPs are the initiators of the process. The results imply on possible zoonosis transmission route of MAP from livestock products to humans. Further research is needed to confirm these results in larger groups of HT patients.